2019
DOI: 10.1111/acer.13992
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion, Alone and in Combination with Naltrexone, Blunts Binge‐Like Ethanol Drinking and Intake Following Chronic Intermittent Access to Ethanol in Male C57BL/6J Mice

Abstract: Background: Regular binge drinking is associated with numerous adverse consequences yet the U.S. Food and Drug Administration (FDA) has approved only 4 medications for the treatment of alcohol use disorders (AUDs), and none have been specifically targeted for treating binge drinking. Here we assessed the effectiveness of the dopamine/norepinephrine reuptake inhibitor, bupropion (BUP), alone and in combination with naltrexone (NAL), to reduce binge-like and chronic ethanol intake in mice. While BUP is an FDA-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…This is especially important for the current and coming experiments because our preclinical research is testing the two pharmacologically active components of the FDA approved drug Contrave® for its potential use in alcohol treatment. Our results support the potential use of the combinations of BPP+NTX to reduce alcohol consumption in a phase II clinical trial experiment [Navarro et al, 2019], with clear consideration of gender differences. A similar reduction observed with sucrose intake may indicate an off-target effect of the combinations.…”
Section: Discussionsupporting
confidence: 77%
“…This is especially important for the current and coming experiments because our preclinical research is testing the two pharmacologically active components of the FDA approved drug Contrave® for its potential use in alcohol treatment. Our results support the potential use of the combinations of BPP+NTX to reduce alcohol consumption in a phase II clinical trial experiment [Navarro et al, 2019], with clear consideration of gender differences. A similar reduction observed with sucrose intake may indicate an off-target effect of the combinations.…”
Section: Discussionsupporting
confidence: 77%
“…In line with our data, DAGL inhibition by DO34 has been previously shown to reduce operant responding for alcohol (43). The magnitude of effect on EtOH intake observed after DAGL inhibition is comparable to or greater than those observed with clinically available treatments such as Naltrexone (44)(45)(46) and Acomprasate (46,47) in similar rodent models. Moreover, pharmacological DAGL inhibition did not affect sucrose preference, suggesting a lack of generalized effect to natural reward, although female DAGL KO mice do exhibit reductions in sucrose preference under some conditions (23).…”
Section: Discussionsupporting
confidence: 90%
“…NTX is known for its efficacy in reducing high alcohol drinking in relapsing patients (Volpicelli et al, 1992;Kiefer et al, 2003;Jonas et al, 2014). NTX, alone or in combination with other drugs, has been shown to reduce EtOH intake using DID methodology (Kamdar et al, 2007;Tarragón et al, 2012;Ripley et al, 2015;Zhou et al, 2019;Navarro et al, 2019). These results add to an extensive list of studies indicating that NTX reduces EtOH consumption using a variety of methodologies and animal models (Davidson and Amit, 1997;Sharpe and Samson 2001;Fachin-Scheit et al, 2006), including genetically predisposed EtOH-preferring strains of rodents such as B6 mice (Le et al, 1993, Phillips et al, 1997Middaugh et al, 2003;Dhaher et al, 2012).…”
Section: ! 12mentioning
confidence: 77%
“…The opioid receptor antagonist naltrexone (NTX), a compound with high affinity for mu-opioid receptors, is used to treat alcoholism (Volpicelli et al, 1992;Kiefer et al, 2003;Jonas et al, 2014), and in combination with bupropion (marketed as Contrave™) has recently been approved for the treatment of binge-eating disorder and weight-loss management. With B6 mice and a dose range of 2-8 mg/kg, previous data have shown that NTX can reduce EtOH binge-like intake using the DID model, although some sex differences have been reported (Kamdar et al, 2007;Tarragón et al, 2012;Zhou et al, 2019;Navarro et al, 2019). It is important to mention, however, that doses of NTX as high as 10 mg/kg have failed to reduce EtOH intake in mice selected for high blood EtOH levels (HDID lines) obtained using the DID model (Crabbe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%